PENINGKATAN MORALITAS SISWA MELALUI MODEL VALUE CLARIFICATION TEHNIQUE (VCT) PADA PEMBELAJARAN PPKn - Yuslina Yuslina; Edy Purnomo; Erlina Rufaidah (Faculty of Teacher Training and Education, University of Lampung, 2017)
The purpose of this research which is to describe the use of video learning to increase democratic attitude and understanding the material. The kind of research used in this research is research the act of a class action. A procedure done in this report is written with stages of planning, the act of, the implementation of the, observation , and reflection for a decision making in order to further development .The subject of study were students in the class IX public junior high schools 19 Bandar Lampung which totaled 32 students. The research results show that (1) the utilization of learning video can improve democratic attitude students. This is proven with an increase in from the cycle of to the cycle. Nevertheless, there are still five students who still have the attitude the category of democratic students were quite good and (2) the utilization of learning video can improve understanding matter students.Tujuan penelitian ini yaitu untuk mendeskripsikan pemanfaatan video pembelajaran untuk meningkatkan sikap demokratis dan pemahaman materi. Jenis penelitian yang digunakan dalam penelitian ini adalah penelitian tindakan kelas (Classroom Action Research). Prosedur yang dilakukan dalam penelitian ini dilakukan dengan tahapan perencanaan, tindakan, pelaksanaan, observasi, dan refleksi untuk pengambilan keputusan guna pengembangan lebih lanjut. Subjek penelitian adalah siswa di Kelas IX SMP Negeri 19 Bandar Lampung Bandar Lampung yang berjumlah 32 siswa. Hasil Penelitian menunjukkan bahwa (1) pemanfaatan video pembelajaran dapat meningkatkan sikap demokratis siswa. Hal ini dibuktikan dengan adanya peningkatan dari siklus ke siklus. Meskipun demikian, masih ada lima siswa yang masih mempunyai sikap demokratis siswa kategori cukup baik dan (2) pemanfaatan video pembelajaran dapat meningkatkan pemahaman materi siswa.Kata kunci: pemahaman materi, sikap demokratis, video pembelajaran